Body mass index and motor coordination: Non-linear relationships in children 6–10 years - Lopes, Vitor P. (2018)
Background: Given the concern for health-related consequences of an elevated body mass index (BMI; obesity), the potential consequences of a low BMI in children are often overlooked. The purpose was to evaluate the relationship between the BMI across its entire spectrum and motor coordination (MC) in children 6–10 years. Methods: Height, weight, and MC (Körperkoordinationstest für Kinder, KTK test battery) were measured in 1,912 boys and 1,826 girls of 6–10 years of age. BMI (kg/m2) was calculated. KTK scores for each of the four tests were also converted to a motor quotient (MQ). One-way ANOVA was used to test differences in the BMI, individual test items, and MQ among boys and girls within age groups. Sex-specific quadratic regressions of individual KTK items and the MQ on the BMI were calculated. Girls and boys were also classified into four weight status groups using International Obesity Task Force criteria: thin, normal, overweight, and obese. Differences in specific test items and MQ between weight status groups were evaluated by age group in each sex. Results: Thirty-one percent of the sample was overweight or obese, whereas 5% was thin. On average, normal weight children had the highest MQ in both sexes across the age range with few exceptions. Overweight/obese children had a lower MQ than normal weight and thin children. The quadratic regression lines generally presented an inverted parabolic relationship between the BMI and MC and suggested a decrease in MC with an increase in the BMI. Conclusion: In general, BMI shows a curvilinear, inverted parabolic relationship with MC in children 6–10 years.